Opioid Sparing Multimodal Analgesia for Transoral Robotic Surgery: Improved Analgesia and Narcotic Use Reduction. Issue 1 (14th March 2023) - Castellanos, Carlos X.; Paoletti, Marcus; Ulloa, Ruben; Kim, Celeste; Fong, Michelle; Xepoleas, Meredith; Sinha, Uttam; Kokot, Niels; Swanson, Mark S.
Abstract: Objective: To compare postoperative pain scores and opioid consumption in patients after transoral robotic surgery (TORS). Study Design: Single institution retrospective cohort study. Setting: TORS was performed at a single academic tertiary care center. Methods: This study compared traditional opioid‐based and opioid‐sparing multimodal analgesia (MMA) regimens in patients with oropharyngeal and supraglottic malignancy after TORS. Data were obtained from the electronic health records from August 2016 to December 2021. The average postoperative pain scores and total opioid consumption in morphine milligram equivalents were calculated for postoperative days (PODs) 0 to 3. The secondary objectives were to quantify and characterize opioid prescriptions upon hospital discharge. Results: A total of 114 patients were identified for this study, 58 patients in the non‐MMA cohort and 56 in the MMA cohort. Postoperative pain levels in the MMA cohort were statistically lower on POD 0 ( p  = 0.001), POD 1 ( p  = 0.001), and POD 3 ( p  = 0.004). Postoperative opioid consumption decreased significantly in the MMA cohort from 37.7 to 10.8 mg on POD 0 ( p  = 0.002), 65.9 to 19.9 mg on POD 1 ( p  < 0.001), 36.0 to 19.3 mg on POD 2 ( p  = 0.02), and 45.4 to 13.8 mg on POD 3 ( p  = 0.02). The number of patients discharged from the hospital with a prescription for narcotics was significantly lower in the MMA cohort (71.4%) compared with the non‐MMA cohort (98.3%) ( p  < 0.001). Conclusion: Implementation of our MMA pain protocol reduced pain levels and narcotic consumption in the immediate postoperative period.